2019
DOI: 10.3390/fib7120111
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Recycled Steel Fiber Reinforced Concrete in Chloride Environment

Abstract: For structural elements exposed to chloride environments, an important aspect of Recycled Steel Fiber Reinforced Concrete (RSFRC) durability is the corrosion resistance. In the present work, an experimental program was carried out to evaluate the long-term effects of chloride attack on the post-cracking behavior of RSFRC by performing splitting tensile tests and round panel tests. Two RSFRC mixtures defined based on the packing density optimization were produced with a fiber content of 0.8% and 1% per volume o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
“…As for the contribution of fibers, it is controlled by the crack opening displacement w k expressed in Equation (11). Moreover, the present formulation assumes a complete reorientation of fibers crossing the cracked section: regardless of their initial inclination (described by the angles α x,k and α z,k ) they are supposed to exert axial stresses σ f,k depending on both the lateral bond stress τ mobilized throughout the lateral area and the possible contribution F of the hooked end (see Section 3.3).…”
Section: Equilibrium Equationsmentioning
confidence: 99%
“…Fiber-reinforced cementitious composites (FRCCs) are a class of concrete-like material developed in the last two decades with the aim of mitigating the inherent fragility of concrete in tension [1]. Several types of fiber are currently adopted as spread reinforcement in FRCCs, which range from the very common steel fibers [2][3][4][5], to the ones either made of plastics [6] or, more recently, obtained from plants [7,8], or produced by recycling waste tires [9][10][11]. Moreover, FRCCs can also be produced by blending different types of fibers to produce a class of composites often referred to as hybrid-FRCCs (Hy-FRCCs) with the aim to mobilize a synergistic action from each fiber [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several investigations have explored the potential of end-of-life tires by-products in the construction industry, such as the use of recycled steel fibers (RSFs) in the reinforcement of cement-based materials [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], namely, in fiber reinforced concrete (FRC). FRC is being used in slabs and shells, such as the case of flooring and tunneling since the support redundancy of this type of structure favors the occurrence of a high level of stress redistribution during crack propagation, which increases their ultimate load regarding their cracking load [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%